Purinergic receptor antagonism reduces interictal discharges and rescues cognitive function in a mouse model of temporal lobe epilepsy - Nelson Espinosa; Soraya Martín-Suárez; Ariel Lara-Vasquez; Trinidad Montero; Teresa Muro-García; German Fernandez; Juan Manuel Encinas-Pérez; Juan Manuel Encinas-Pérez; Juan Manuel Encinas-Pérez; Pablo Fuentealba (Frontiers in Neuroscience)
Epilepsy is one of the most prevalent neurological disorders globally. Current treatments mainly target neuronal activity, often overlooking the involvement of astrocytes and microglia in epilepsy’s pathophysiology. Here, we explored the impact of purinergic receptors, predominantly found in glial tissue, on epileptiform activity. We used TNP-ATP, a potent purinergic receptor antagonist, and conducted experiments using a mouse model of mesial temporal lobe epilepsy to examine behavioral performance and neural activity patterns. Our findings reveal that although TNP-ATP treatment did not significantly impact motor function or anxiety levels, it reduced both the amplitude and rate of hippocampal interictal discharges. Such reduction also affected the synchrony of associated neuronal spiking. Additionally, cognitive function, particularly hippocampus-dependent spatial memory and prefrontal cortex-dependent executive control, were partially restored. Moreover, neuronal recordings showed increased phase coherence between the hippocampus and prefrontal cortex for both slow (theta) and fast (gamma) oscillations in treated animals, indicating strengthened neural coordination between cortical regions upon purinergic receptor antagonism. These results underscore the potential role of purinergic receptor antagonists in improving behavioral and cognitive performance in epilepsy, providing novel insight into the use of these pharmacological agents as a therapeutic approach.